17(S),18(R)‐epoxyeicosatetraenoic acid generated by cytochrome P450 BM‐3 from Bacillus megaterium inhibits the development of contact hypersensitivity via G‐protein‐coupled receptor 40‐mediated neutrophil suppression - Azusa Saika; Takahiro Nagatake; Shigenobu Kishino; Si‐Bum Park; Tetsuya Honda; Naomi Matsumoto; Michiko Shimojou; Sakiko Morimoto; Prabha Tiwari; Eri Node; So‐ichiro Hirata; Koji Hosomi; et al. (FASEB BioAdvances, 2020)
Abstract Dietary intake of ω3 polyunsaturated fatty acids such as eicosapentaenoic acid and docosahexaenoic acid is beneficial for health control. We recently identified 17,18‐epoxyeicosatetraenoic acid (17,18‐EpETE) as a lipid metabolite endogenously generated from eicosapentaenoic acid that exhibits potent anti‐allergic and anti‐inflammatory properties. However, chemically synthesized 17,18‐EpETE is enantiomeric due to its epoxy group—17(S),18(R)‐EpETE and 17(R),18(S)‐EpETE. In this study, we demonstrated stereoselective differences of 17(S),18(R)‐EpETE and 17(R),18(S)‐EpETE in amelioration of skin contact hypersensitivity and found that anti‐inflammatory activity was detected in 17(S),18(R)‐EpETE, but not in 17(R),18(S)‐EpETE. In addition, we found that cytochrome P450 BM‐3 derived from Bacillus megaterium stereoselectively converts EPA into 17(S),18(R)‐EpETE, which effectively inhibited the development of skin contact hypersensitivity by inhibiting neutrophil migration in a G protein‐coupled receptor 40‐dependent manner. These results suggest the new availability of a bacterial enzyme to produce a beneficial lipid mediator, 17(S),18(R)‐EpETE, in a stereoselective manner. Our findings highlight that bacterial enzymatic conversion of fatty acid is a promising strategy for mass production of bioactive lipid metabolites.